About projection-selection-join queries addressed to possibilistic relational databases. - Bosc, P. (IEEE Transactions on fuzzy systems)
This work deals with databases containing ill-known attribute values represented by possibility distributions. Any such database has a canonical interpretation as a set of regular databases, but it is well known that their manipulation raises a number of problems, in particular with respect to the soundness of querying operations and the tractability of the evaluation process. In This work, we propose a query language including three operators which are soundly defined on extended possibilistic (compact) relations, which is the key for tractability. The originality of the approach is twofold: 1) a nesting mechanism is introduced in the data model in order to support the expression of the result of some of the operations allowed, and 2) a joint operation enables to compose possibilistic relations under some reasonable hypotheses.